Kinetic Analysis of the Adsorption of the Brominated Flame Retardant 4-bromodiphenyl Ether onto Biochar-immobilized Sphingomonas sp. (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2019)
4-bromophenyl phenyl ether or 4-bromodiphenyl ether (4-BDE) is a less brominated PBDE, which are brominated flame retardants (BFRs), that has come into importance when it was detected as the main pollutant in Sungai Buah, a tributary to the Sungai Semenyih that have recently caused the pollution of drinking waters in the Semenyih Water Treatment Plant, Putrajaya Selangor that led to water shortage for many days to affecting many areas. 4-BDE is also a recalcitrant priority pollutant where it is barely degraded at all. Many of the PBDE can cause developmental neurotoxicity. The absorption kinetics data of biosorption isotherm on the biosorption of 4-BDE onto Biochar-immobilized Sphingomonas sp. were analyzed using three models—pseudo-1st, pseudo-2nd and Elovich, and fitted using non-linear regression. The Elovich model was the poorest in fitting the curve based on visual observation followed by the pseudo-1st order. Statistical analysis based on root-mean-square error (RMSE), adjusted coefficient of determination (adjR2), bias factor (BF), accuracy factor (AF), corrected AICc (Akaike Information Criterion), Bayesian Information Criterion (BIC) and Hannan–Quinn information criterion (HQC) that showed that the pseudo-1ST order model is the best model. Kinetic analysis using the pseudo-1st order model at 400 mg/L 4-BDE gave a value of equilibrium sorption capacity qe of 31.89 mg g-1 (95% confidence interval from 30.37 to 33.42) and a value of the pseudo-1st-order rate constant, k1 of 0.22 (95% confidence interval from 0.019 to 0.025). Further analysis is needed to provide proof for the chemisorption mechanism usually tied to this kinetic.
Keywords: Biosorption; kinetics; 4-bromodiphenyl Ether; Biochar-Immobilized; Sphingomonas sp.